Clinical utility of folate-containing oral contraceptives [Corrigendum] - Lassi ZS; Bhutta ZA (Dove Medical Press, 2013)
Lassi ZS, Bhutta ZA. International Journal of Women’s Health. 2012;4:185–190.On page 185, Burden of neural tube defects and its natural history section, 3rd paragraph, 1st sentence, note that "estimated incidence of 4,300,000 new cases a year" should have been "estimated incidence of >300,000 new cases a year".On page 189, Reference 2 was listed as Jegatheesan P, Keller RL, Hawgood S. Early variable-flow nasal continuous positive airway pressure in infants ≤1000 grams at birth. J Perinatol. 2006;26(3):189–196.The correct reference is Shibuya K, Murray CJL. Congenital anomalies. In: Murray CJL, Lopez AD, eds. Health Dimensions of Sex and Reproduction: The Global Burden of Sexually Transmitted Diseases, HIV, Maternal Conditions, Perinatal Disorders, and Congenital Anomalies. Vol. 3. Boston, MA: Harvard University Press, 1998:455–512.Read the original article